Fastening fabric structure - CHOU CHAO-MU (2014)
A fastening fabric structure is disclosed to have a micro-fibriform loop fabric, fabricated by complex, textured micro-fiber yarn and split thereafter to recover more and smaller fibers, all of the fibers forming the micro-fibriform loops or pile loops between the inter-weaving or inter-knitting nodes, and a fibriform pile fabric, fabricated by spun yarn or synthetic filament yarn and sheared to form erected, dispersed non-hook fiber bundles of micro-fibriform pile for fastening the micro-fibriform loops of said micro-fibriform loop fabric. The erected, dispersed non-hook fiber bundles of micro-fibriform pile will not be tangled together, enhancing the fastening ability of the fastening fabric.